Peningkatan Hasil Belajar Fisika di Era Digital: Peran Learning Management System di Sekolah Penggerak - Fauziyyah, Salma Arfa; Mulvia, Rahmadhani; Lestari, Isti Fuji (Jurnal Pendidikan dan Ilmu Fisika, 2024)
This study aims to analyze the impact of utilizing a Learning Management System (LMS) on high school students' Physics learning outcomes, focusing on the topic of work and energy. Employing a quasi-experimental design, this research compares two groups of students: an experimental group using LMS and a control group following conventional teaching methods. Data were collected through pretests and posttests to measure learning outcomes, and statistical analysis was conducted to examine the differences between the two groups. To strengthen data analysis, qualitative data were gathered through interviews with students and teachers. The findings indicate that the experimental group using LMS experienced a significant improvement in their understanding of Physics concepts compared to the control group, with the N-Gain score for the experimental group falling within the moderate improvement category. Furthermore, despite certain challenges in LMS implementation, such as technological infrastructure readiness and teacher competence, this study demonstrates that LMS holds great potential in enhancing student engagement and improving learning effectiveness. Therefore, it is recommended to expand the adoption of LMS in Indonesian schools as part of the technology-driven educational transformation.